Comparing Subcuticular and Transdermal Appendectomy Repairs: A Randomized Clinical Trial - Malekpour Alamdari, Nasser; Shahbazzadeh, Amir; Gholizadeh, Barmak (International Journal of Medical Toxicology and Forensic Medicine, 2018)
Background: Appendectomy is one of the most common abdominal operations. The prevalence of appendicitis increases with increased lymphatic tissue with the maximum prevalence at the beginning of adulthood. Owing to the high prevalence of appendectomy, patients will be benefited from a better method with improvement of surgical site and management of postoperative pain and infection. Subcuticular repair method due to better scar formation and less pain is preferred to the routine repair method, if the infection rate is comparable. Methods: The current study was conducted on appendectomy candidates in 2017. After providing the necessary explanations, the interested patients signed the informed consent forms and voluntarily participated in the study. The subjects were randomly assigned into two groups of randomized clinical trial with parallel design and 1:1 ratio. The sample size was 120 individuals based on previous studies. Subjects were assigned into two groups of 105 subjects each: the first group as subcuticular and the second group as transdermal accordingly. Then, they were studied and followed up. Results: One week after operation, 8.5% of subcuticular and 5.7% of transdermal repairs developed localized infection, and no significant difference was observed between the two groups. One week after surgery in the first group, 10% had no pain, 36% mild pain, 27% moderate pain, and 27% severe pain. In the second group, 7% had no pain, 36% mild pain, 30% moderate pain, and 27% severe pain. Therefore, there was no significant difference between two groups in this regard. Conclusion: There was no significant difference in the surgical wound infection rate between two methods. Accordingly, subcuticular repair was suggested as the preferred method owing to its better scar formation.